Cytotoxic Activity of /V-alkyl and /V-benzyl 1,10-phenathroline derivatives in Human Cancer Cell Lines - Isnatin Miladiyah, Esti Nurwening Sholikhah Mustofa (Universitas Gadjah Mada, 2007)
Background: In our study on the antiplasmodial activity of 1,1 O-phenanthroline derivatives, we found some compounds possessing a potential cytotoxic in normal cell line.Objective: In this study we tested these derivatives in human cancer lines in order to know their in vitro anticancer activity.Materials and methods: Six derivatives of 1,1 O-phenanthroline, 4 derivatives of N-alkyl and 2 derivatives of N-benzyl 1,1 O-phenanthroline were tested on two human cells cancer, myeloma (NS-1) and HeLa cells line. Cytotoxic activity was evaluated by trypan blue exclusion assay and their activity was expressed by the concentration inhibiting 50% of the cell growth (lCso) The ICso of each compound was determined by probit analysis.Results: The results showed that the ICso values of 1,1 O-phenanthroline derivatives ranged from 4.68 to 15.63 pM on myeloma cell and from 2.82 to 16.89 pM on HeLa cell. The 4-Bromo-3(2-bromoetyll-2metyl-1 , 1 O-phenantroline (3) and (1 )-N-(4-benzyloxy-3-methoxy-benzyll-1 ,1 O-phenanthrolinium chloride (6) with ICso values ranged from 4.68 to 4.72 pM on myeloma cell showed the same (p>0.05) cytotoxicity with doxorubicin, with ICso values ranged from 2.82 to 3.08 pM on HeLa cell showed the higher (p